TOWARD INTIMATE DATA: RE-THINKING DIGITAL, SOCIAL, POLITICAL RELATIONS - Burns, Ryan; Hoffmann, Anna Lauren; Welker, Preston (AoIR Selected Papers of Internet Research, 2023)
Digital technologies enable the mass datafication of human activity in new and intimate ways, allowing for both active and passive tracking bodily functions, physical movements, consumption habits, social encounters, and even moods and feelings. Despite the seeming newness of these developments, however, Internet scholars recognize that data production and use has always been bound up with broader relations between individuals, communities, and claims to the privateness or publicness of certain bodies, spaces, and behaviors. Most recently, critical data scholars have illuminated the complex, often surreptitious contexts in which datafication occurs, offering a range of conceptual frameworks to contend with the meanings and implications of these deeply personal digital-human entanglements. In this paper we take up and recast the notion of “intimate data.” Elsewhere denoting a particular category of tracked activities deemed private or sensitive, we instead consider intimacy as marking a set of (often unequal) socio-political relationships. That is, we mobilize “intimate data” to attend to the processes by which individuals and collectives are datafied in ways that have repercussions for knowledges about oneself and others. In so doing, we sidestep hermetic liberal conceptions of data that center ideals like consent and exchange to think about data collection as eliciting confessions , vulnerabilities, monetizable practices, and new possibilities for governing (inter)personal and other relations. We advance different, alternative political responses, focusing specifically on (1) the (racialized, gendered, classed, sexualized) normativity of intimate data, (2) (re)considerations of privacy and surveillance, (3) tensions around visibility, and (4) responsibilization of individuals to police spaces.